Persepsi Mahasiswa Terhadap Pembelajaran Daring - Sapto Irawan; Listyaningsih Listyaningsih (Program Studi Pendidikan Guru Sekolah Dasar, Universitas Kristen Satya Wacana, 2021)
This study aims to describe students’ perceptions towards online learning. This research uses a quantitative descriptive approach. The data was collected was through questionnaire by adopting the Maulana and Hamidi (2020) instrument which measures three aspects, namely aspects of teaching and learning, capabilities or abilities of lecturers, and infrastructure. The subjects of this study were the Satya Wacana Christian University Guidance and Counseling Study Program students with a sample of 135 students. The results showed that overall in the teaching and learning aspect as many as 77 students or an average percentage of 57% said that in the medium category, the capability aspect (lecturer ability) was 81 students or the average percentage of 60% said it was in good category, and in the aspect of facilities and infrastructure as much as 67 students or an average percentage of 50% said that the facilities and infrastructure for online learning were in the medium category.